Double burden of vulnerability for refugees: conceptualization and policy solutions for financial protection in Iran using systems thinking approach - Saeed Shahabi; Manal Etemadi; Maryam Hedayati; Kamran Bagheri Lankarani; Mihajlo Jakovljevic (BMC, 2023)
Abstract Introduction Iran is host to one of the world's largest and longest-standing refugee populations. Although Iran has initiated a basic health insurance scheme for refugees throughout the country since September 2015, the population coverage of this scheme is very low, and various factors have caused a significant percentage of refugees to still lack insurance coverage and often face financial hardships when receiving health services. In response, this study aimed to understand barriers to insurance coverage among refugees in Iran and propose effective policies that can address persistent gaps in financial protection. Methods This qualitative study was conducted in two phases. First, a review of policy documents and interviews with participants were conducted to investigate the common barriers and facilitators of effective insurance coverage for refugees in Iran. Then, a systems thinking approach was applied to visualize the common variables and interactions on the path to achieving financial protection for refugees. Results Findings showed that various factors, such as (1) household-based premium for refugees, (2) considering a waiting time to be eligible for insurance benefits, (3) determining high premiums for non-vulnerable groups and (4) a deep difference between the health services tariffs of the public and private service delivery sectors in Iran, have caused the coverage of health insurance for non-vulnerable refugees to be challenging. Furthermore, some policy solutions were found to improve the health insurance coverage of refugees in Iran. These included removing household size from premium calculations, lowering current premium rates and getting monthly premiums from non-vulnerable refugees. Conclusions A number of factors have caused health insurance coverage to be inaccessible for refugees, especially non-vulnerable refugees in Iran. Therefore, it is necessary to adopt effective policies to improve the health financing for the refugee with the aim of ensuring financial protection, taking into account the different actors and the interactions between them.